Pengaruh kesepian terhadap kecenderungan internet gaming disorder pada pemain battle royale game - Abdul Gafur Mursyad; Diah Karmiyati; Diana Savitri Hidayati (Fakultas Psikologi, 2019)
Online games in this era can be played with mobile phones. One of the most popular mobile games today is the battle royale game. The frequent play of online games over period of 12 months can cause players to tend to internet gaming disorder. One factor that is though to affect the frequency of playing online games is loneliness. The purpose of this study was to determine the effect of loneliness on tendency of internet gaming disorder. This research is a quantitative non-experimental regression form. The subject of this study amounted to 103 subjects with the characteristics of playing battle royale game at least 4.5 hours per day and aged 18 to 25 years obtained by accidental sampling technique. The scale of this study uses the De Jong Gierveld Loneliness scale developed by researchers to measure the loneliness and scale of Internet Gaming Disorders to measure the tendency of internet gaming disorder. The results of a simple regression analysis results of the coefficient of determination (r2) 0.066 with sig (p) 0.009 (p <0.01) and the correlation coefficient yield (r) 0.258 which shows a positive influence between the choice tendency of internet gaming disorder in players with battle royale 6.6%.